Blue elixir of youth and wellness: The multicomponent-multitarget paradigm of Curcuma caesia Roxb - Sabrina Burattini; Federico Gianfanti; Francesco Onesimo; Sabrina Donati Zeppa; Barbara Canonico; Mariele Montanari; Giovanna Panza; Daniele Lopez; Giosuè Annibalini; Fabiana Fanelli; Roberta Saltarelli; Michele Mari; et al. (Journal of Functional Foods)
Aging is a complex biological process influenced by genetic, environmental, and lifestyle factors, including diet and exercise. This process not only leads to visible signs of skin aging, such as wrinkles and elasticity loss, but also predisposes individuals to a spectrum of age-related diseases. Oxidative stress and inflammation are key events driving this phenomenon. This study aims to delve into the antioxidative and protective potential of a rhizome extract from Curcuma caesia Roxb., a less explored species within the turmeric family, focusing on its effects on HaCaT cells subjected to UV radiation. Curcuma caesia Roxb. rhizome was extracted for a phytocomplex (CCRE). Through HPLC-ESI-MS/MS, the chemical analysis identified key phenolic compounds, including (−)-epicatechin, procyanidin B2, and p-coumaric acid. Human immortalized keratinocyte cell lines (HaCaT) were treated with CCRE in healthy and UVB-induced conditions to assess their impact on oxidative stress and aging. Results demonstrated a significant reduction in mitochondrial superoxide anion levels without affecting mitochondrial membrane potential, indicating enhanced cellular resilience to oxidative stress. Additionally, CCRE decreased UVB-induced IL-6 expression and IKK phosphorylation, which play a crucial role in inflammaging. Notably, CCRE treatment also improved cell viability upon UVB exposure and mitigated UVB-induced cell apoptosis, further underscoring its potential to preserve cellular integrity and function in relation to environmental stressors. CCRE chemical composition and biological effects position it as a potential ingredient for formulations and functional foods to combat the signs of skin aging and enhance overall skin health.